Adolescent Smoking and Its Association with Poor Nutritional Outcomes in Rural Pamekasan, Indonesia - Bahmid, Moh; Bagus Qomaruddin , Moh; Fatah, Zainal (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2024)
This study investigated the relationship between active smoking and nutritional status among male adolescents aged 14-16 years in Kertagena Tengah Village, Kadur District, Pamekasan, Indonesia. A cross-sectional study design was employed, and a total of 55 adolescents were included using a total sampling technique. Smoking status was assessed using standardized questionnaires, while nutritional status was determined using anthropometric measurements, including body mass index (BMI). The study found that 76% of the adolescents were active smokers, with 69% of them being classified as undernourished. A significant relationship was observed between active smoking and poor nutritional status (p=0.018). The main contributing factors to poor nutritional status included an unbalanced diet, lack of access to nutritious food, and high smoking rates among adolescents. Smoking was found to reduce appetite and interfere with nutrient absorption, exacerbating nutritional deficiencies. The study highlights the urgent need for comprehensive public health interventions, including health education, stricter regulation of cigarette sales to minors, and community support to create a smoke-free environment. Future research should include longitudinal studies to clarify the causal link between smoking and nutritional status, broaden demographic coverage, and incorporate qualitative methods to explore the social and cultural influences on adolescent smoking.